Antiapoptotic effect of leu-enkephalin neuropeptide on donor blood leukocytes under cold stress - Gulevsky, A.K.; Moiseyevа N.N.; Gorina, O.L. (Reports of the National Academy of Sciences of Ukraine, 2019)
Using various modes of cold stress, the degree of apoptosis depending on the duration of cold exposure and the temperature is determined. The influence of leu-enkephalin regulatory neuropeptide on the development of leukocyte apoptosis of human donor blood after cold stress by morphological indices is studied. The fluorescence microscopy and Hoechst 33342 and PI dyes were used. It has been proved that the addition of the neuropeptide in a concentration of 10−9 Mol to leukocytes, which were subjected to cold stress, significantly reduces the number of apoptotic cells.